Conference on Interaction and ConfidenceBuilding Measures in Asia: A Systematic Approach to Ensuring Regional Security in the New Context of International Legal Issues (Part II) - Zh. M. Amanzholov (Московский журнал международного права, 2009)
Kazakhstan’s foreign policy initiative to convene the Conference on Interaction and Confidence-Building Measures in Asia (CICBMA) is a response to the existing need to create a unified regional system of collective security and cooperation. Such a conference is necessary because, unlike other continents, Asia still lacks a properly functioning mechanism of legal control and regulation. The activities of international institutions operating in this part of the globe are mostly sub-regional and closed in their nature. Therefore, it is necessary not only to establish an inter-regional dialogue between these institutions, but also unite them under a single regional organization.